Efficacy of Synthetic Peptide Corresponding to the ACTH-Like Sequence of Human Immunoglobulin G1 in Experimental Autoimmune Encephalomyelitis - Turobov, Valery I.; Danilkovich, Alexey V.; Shevelev, Alexei B.; Biryukova, Yulia K.; Pozdniakova, Natalia V.; Azev, Viatcheslav N.; Murashev, Arkady N.; Lipkin, Valery M.; Udovichenko, Igor P. (Frontiers in Pharmacology, 2018)
Peptide immunocortin sequence corresponds to the amino acid residues 11-20 of the variable part of human immunoglobulin G1 (IgG1) heavy chain. Since immunocortin was shown previously to inhibit phagocytosis in peritoneal macrophages and ConA-induced T-lymphocytes proliferation in culture, we suggested that immunocortin administering may be of use for patients with self-immune syndrome. Immunocortin in concentration 10 µM inhibited proliferation of both antigen (myelin)-induced and ConA-induced LN lymphocytes isolated from the lymph nodes of Dark Agouti (DA) rats immunized with chorda shear. The biological trials of the synthetic immunocortin were carried out on the DA rats with induced experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. These in vivo experiments have shown that intraperitoneal injections of immunocortin in a daily dosage 100 µg per animal reduced symptoms of EAE in DA rats.